Effects of elevated CO2 and water stress on root structure and hydraulic conductance of Solanum melongena L - Sarker, Bikash C; Hara, Michihiro (Bangladesh Journal of Botany, 2010)
Pot experiment was conducted using eggplants (Solanum melongena L.) grown in a controlled growth chamber environment. Ambient (370 ppm) and elevated (700 ppm) CO2 concentrations, were used. Hydraulic conductance in stressed eggplants was lower than that of control eggplants and this phenomenon was enhanced under elevated CO2 environment and also due to plant age. Hydraulic conductance through the root system in free water was comparatively higher than that of soil medium. As in the pressure plate apparatus technique with moist soil, the eggplants that experienced repetitively shorter stress showed the lowest conductance (6.38 × 10-5 kg/m2/s/MPa) under the interactive effects of high CO2 and water stress while control and longer stressed plants had 9.11 × 10-5 and 7.19 × 10-5 kg/m2/s/MPa, respectively. It appeared that eggplants grown in a high CO2 environment might be efficient in water use under soil water shortage conditions. Key words: Solanum melongena; Hydraulic conductance; Root structure; Water stress DOI: 10.3329/bjb.v38i1.5125 Bangladesh J. Bot. 38(1): 55-63, 2009 (June